2013
DOI: 10.1093/aob/mct063
|View full text |Cite
|
Sign up to set email alerts
|

Nectar secretion on fern fronds associated with lower levels of herbivore damage: field experiments with a widespread epiphyte of Mexican cloud forest remnants

Abstract: The long evolutionary history of ferns may explain why some previous studies of fern nectaries have shown little or no benefit to ferns from nectary visitors, as any coevolved herbivores are those resistant to ant defence. The results suggest that ants protect Pl. crassinervata fronds against herbivory. The presence of nectaries, and the relationship with ants, may contribute to this fern's widespread occurrence and persistence in the face of disturbance, though many other factors also play a role. Ant defence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
0
32
0
2
Order By: Relevance
“…Leaf damage and the consequent increase in EFN production resulted in higher ant attendance in S. chapmanii . Extrafloral nectar is widely known to mediate food for protection mutualisms between ants and plants, and many plants have been shown to derive significant fitness benefits from these interactions (Koptur, 1979; Oliveira, 1997; Rudgers, 2004; Koptur et al, 2013). The majority of studies, however, have used an all or nothing exclusion of ants or of EFN (Rosumek et al, 2009), and few have demonstrated a correlation between investment in EFN production and the intensity of ant–plant interactions (but see Heil et al, 2001; Kost and Heil, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf damage and the consequent increase in EFN production resulted in higher ant attendance in S. chapmanii . Extrafloral nectar is widely known to mediate food for protection mutualisms between ants and plants, and many plants have been shown to derive significant fitness benefits from these interactions (Koptur, 1979; Oliveira, 1997; Rudgers, 2004; Koptur et al, 2013). The majority of studies, however, have used an all or nothing exclusion of ants or of EFN (Rosumek et al, 2009), and few have demonstrated a correlation between investment in EFN production and the intensity of ant–plant interactions (but see Heil et al, 2001; Kost and Heil, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Janzen (1966) famously observed that Acacia cornigera plants succumbed to herbivory when resident ants ( Pseudomyrmex ferruginea ) were experimentally removed. Plants that provide only EFN are normally involved only in facultative interactions with ants; however, significant fitness benefits have been reported nonetheless (Koptur, 1979, 1984; Oliveira, 1997; Rudgers, 2004; Koptur et al, 2013).…”
mentioning
confidence: 99%
“…Weber and Keeler (2013) estimated that extrafloral nectaries have evolved independently at least 457 times in vascular plants. Even among the ferns, extrasoral nectaries have arisen independently several times, and they first evolved long before floral nectar and long before ants appeared in the fossil record (Marazzi et al 2012;Koptur et al 2013). Therefore, their original function could not have involved ants or other social hymenopterans.…”
Section: Gunnera Symbiosismentioning
confidence: 99%
“…The function of EFNs has been proposed as either a plant defence mechanism attracting insect predators and parasitoids, or a diversion to keep insects away from the floral nectary sources (Bentley, 1976;Stephenson, 1982;Wagner & Kay, 2002;González-Teuber & Heil, 2009). In either case, EFNs are highly attractive to ants and often facilitate a mutualistic ant-plant relationship (Heil et al, 2001;Díaz-Castelazo et al, 2013;Koptur et al, 2013). Some of these ant-plant relationships become obligate associations, with EFN nectar tailored to attract and provide nourishment for only their resident ant species (Heil et al, 2005).…”
Section: Introductionmentioning
confidence: 99%